Who do you want your customers to become? - Schrage, Michael (Boston, Massachusetts : Harvard Business Review Press, 2012)
Who do you want your customers to become? According to MIT innovation expert and thought leader Michael Schrage, if you aren't asking this question, your strategic marketing and innovation efforts will fail. In this latest HBR Single, Schrage provides a powerful new lens for getting more value out of innovation investment...
Title from PDF title page (viewed on Feb. 20, 2014).
Keywords: Relationship marketing; Customer relations; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books